Synthesis of Highly Substituted Cyclobutanones by a One‐Pot Keteniminium‐Enamine Process. Issue 5 (16th April 2021) - Dagoneau, Dylan; Kolleth, Amandine; Quinodoz, Pierre; Horoz, Beyza; Catak, Saron; Lumbroso, Alexandre; Sulzer‐Mossé, Sarah; De Mesmaeker, Alain
Abstract: Herein, we describe an effective one‐pot sequence for the regio‐ and stereoselective synthesis of highly substituted cyclobutanones. This process relies on first a [2+2] cycloaddition involving a keteniminium salt intermediate with an alkene followed by isomerization of the resulting cyclobutaniminium salt into its cyclic enamine form and then reaction of the latter with an electrophile. The adduct can be either hydrolyzed or reduced to give the corresponding cyclobutanone or cyclobutanamine, respectively, with excellent diastereocontrol. A variety of electrophiles was tolerated allowing the incorporation of diverse substituents and functionalities onto the cyclobutyl ring. Additionally, the coplanarity of diverse cyclic enamines was investigated through a DFT study. Abstract :